'Half-hearted tokens of transparent love?' Ethnic postcards and the visual mediation of host-tourist communication - Thurlow, Crispin; Jaworski, Adam; Ylänne, Virpi (Cognizant Communication, 2005)
One negotiation site of heavily mediated, indirect, and usually inadvertent communication between hosts and tourists is the picture postcard rack. As “hegemonically scripted discourses,” postcards make important assumptions about the tourist’s touristic experience, as well as the image of that experience she/he will want to communicate to others “back home.” Of more importance, however, are the assumptions being made in postcards about the people actually represented in them. Certainly, postcard images of local people (locals rather than necessarily hosts) are often designed specifically to communicate their ambassadorial hospitality—their host-like qualities—and to promote the kind of ethnotourism discussed widely in the tourism literature. Nowhere is this more apparent than in the postcard images of local ethnic minority people such as the Zulus in South Africa and the Sámi in Finland. In these two instances of intense exoticization and commodified cultural representation, and in stark contrast to postcard images of the Welsh in Britain, this study was interested in exploring the ways in which both the “represented host” and “consumer tourist” understand and view these visual representations. In this programmatic article, we therefore report our initial analyses of three distinctive sets of postcards as a means for discussing how research might seek to situate and, thereby, complicate assumptions inherent in these “ethnic” postcards about both the traversed, mediatized Other, and the constantly directed tourist gaze.